Negative pole piece, manufacturing method of negative pole piece, secondary battery comprising negative pole piece, and electric device comprising negative pole piece
By providing a coating and a polymer layer including porous particles on the conductive coating of the negative electrode-free battery, the problem of volume expansion and uneven deposition during lithium/sodium deposition is solved, and the higher cycle stability and lower gas yield of the battery are achieved.
Patent Information
- Application Number
- CN202311359432.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-19
- Publication Date
- 2025-04-22
AI Technical Summary
The volume expansion and uneven deposition problems caused by the lithium/sodium deposition process in the negative electrode battery lead to the battery's bloating easily and the cycle life is low.
A coating including porous particles is provided on the conductive coating, providing a larger expansion space and more nucleation sites, promoting uniform deposition of lithium/sodium, and forming a polymer layer on the surface of the coating to accelerate metal ions transfer and charge transfer.
It effectively reduces the volume expansion during lithium/sodium deposition, inhibits the generation and side reaction of hydrogen at the interface, improves the uniform deposition of lithium/sodium, extends the cycle life of the battery, and reduces the gas production of the battery.
Smart Images

Figure BDA0004506572880000191 
Figure BDA0004506572880000201 
Figure BDA0004506572880000211
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of secondary batteries, and in particular to a negative electrode sheet for a negative electrode-free battery and a manufacturing method thereof, a secondary battery including the negative electrode sheet, and an electrical device. Background Art
[0002] In recent years, a new type of anode-free metal battery has emerged, which greatly improves the battery energy density by not using negative electrode active materials. This battery system deposits lithium / sodium in the positive electrode material on the negative electrode current collector through formation charging. However, there are problems of volume expansion caused by deposition and uneven deposition caused by uneven surface of the current collector during the lithium / sodium deposition process, which in turn cause the following problems:
[0003] Easy to bloat: Due to the volume expansion during the lithium / sodium deposition process, it is difficult to form a stable SEI on the negative electrode surface, which will cause side reactions between the highly active lithium / sodium and other components of the battery and the generation of hydrogen at the interface, thus causing battery bloating and battery failure;
[0004] Cycle life: Due to uneven lithium / sodium deposition, dendrites and dead lithium / sodium will be formed during the battery charge and discharge process, resulting in a low battery cycle life.
[0005] Therefore, it is necessary to further improve the negative electrode plate to at least alleviate some of the above problems. Summary of the invention
[0006] The present application is made in view of the above-mentioned problems, and aims to provide a negative electrode sheet, which is optionally applicable to a negative electrode-free battery, and includes a coating including porous particles disposed on a conductive coating. At the same time, the present application also relates to a method for manufacturing the above-mentioned negative electrode sheet, a secondary battery including the negative electrode sheet, and an electrical device including the secondary battery.
[0007] In order to achieve the above-mentioned object, the present application provides a negative electrode plate, comprising: a negative electrode current collector; a conductive coating disposed on at least one surface of the negative electrode current collector; and a coating comprising porous particles disposed on the surface of the conductive coating. As described above, by disposing a coating comprising porous particles on the surface of the conductive coating, on the one hand, a larger expansion space is provided, reducing the volume expansion caused by the lithium / sodium deposition process; on the other hand, more nucleation sites are provided, and the more sites there are, the more inclined to form a plane, thereby promoting the uniform deposition of lithium / sodium.
[0008] In any embodiment, the surface density of the coating is 0.002 g / 1540 m 2 To 0.02g / 1540m 2If the surface density is too low, the process conditions cannot be met; if the surface density is too high, the energy density will be affected. When the coating surface density is within this range, the energy density can be affected as little as possible within the existing process conditions.
[0009] In any embodiment, the average particle size Dv50 of the porous particles is 0.2 μm to 10 μm, optionally 0.5 μm to 5 μm, for example 0.5 μm to 2 μm. The average particle size of the particles affects the thickness of the coating. In theory, the thickness of the coating should be as thin as possible to facilitate the overall performance of the battery while achieving the above functions, and is optionally less than 10 μm. The average particle size of the porous particles within the above range is conducive to forming a coating with a thickness of less than 10 μm.
[0010] In any embodiment, the porous particles have a porosity of 40% to 60%, and optionally a porosity of 45% to 55%. When the porosity of the porous particles is within this range, sufficient and stable expansion space is reserved for the volume change caused by metal deposition, which can effectively inhibit the generation of hydrogen at the interface and the occurrence of side reactions.
[0011] In any embodiment, the porous particles include at least one of porous metal or porous metal oxide, inorganic porous material and porous polymer; and optionally include at least one of porous metal or porous metal oxide. The material of the porous particles itself is not particularly limited, as long as its porous structure itself can provide sufficient nucleation sites to facilitate the uniform deposition of lithium / sodium.
[0012] In any embodiment, the porous metal or porous metal oxide includes gold (Au), silver (Ag), platinum (Pt), zinc (Zn), zinc oxide (ZnO), copper (Cu), copper oxide (CuO), tin (Sn), tin oxide (SnO), antimony (Sb), antimony oxide (SbO), 2 O 3 , Sb 2 O 5 ), bismuth (Bi), bismuth oxide (Bi 2 O 3 ) and aluminum oxide (Al 2 O 3 ). In any embodiment, the inorganic porous material includes at least one of porous carbon and porous ceramic. In any embodiment, the porous polymer includes at least one of porous polyacrylic acid, porous polyacrylamide, porous polyacrylonitrile, and porous polyimide. These materials are commercially available, such as from HQJX, Zhongke Keyou, McLean, etc., so the coating of the present application can be obtained at a lower cost.
[0013] In any embodiment, the thickness of the coating layer including the porous particles is 2 μm to 10 μm, and optionally 3 μm to 5 μm. Taking into account the effect of the coating thickness on the cost, gas production, and cycle life, while achieving the above functions, reducing the coating thickness as much as possible will be beneficial to the overall performance of the battery. When the coating thickness is within the above range, the coating is intact and not prone to cracks.
[0014] In any embodiment, the conductive coating includes a conductive agent. In the present application, the conductive agent used is not particularly limited, and the conductive agent may include at least one of carbon nanotubes, graphite, conductive carbon black, acetylene black, Ketjen black, carbon fiber or graphene. By providing a conductive coating on the surface of the negative electrode current collector, the conductivity of the electrode sheet can be improved, thereby reducing the internal resistance and improving the conductivity of the entire battery system.
[0015] In any embodiment, the thickness of the conductive coating is 2 μm to 20 μm. Within this range, the provision of the conductive coating will not cause excessive energy density loss, and will not fail to play a corresponding role due to uneven distribution.
[0016] In any embodiment, the negative electrode plate further includes: a polymer layer disposed on the coating layer including porous particles. Optionally, the material of the polymer layer includes a group that can form intermolecular forces (such as hydrogen bonds) with molecules in the system in which it is located, and is further optionally selected from at least one of polyacrylic acid, polyacrylamide, polyacrylonitrile and polyimide. Due to its chain structure, the polymer will not occupy the pores of the porous particles; and by forming a polymer layer, it plays a role similar to a "filter membrane", selectively allowing particles of the size of Li+ / Na+ ions to pass through. In addition, since the polymer layer is uniformly coated on the electrode surface, the wettability of the electrolyte to the electrode is improved. In addition, strong intermolecular interactions, such as hydrogen bonds, occur between the groups in the polymer (such as NH, C=O) and the electrolyte, thereby accelerating the charge transfer process of Li+ / Na+ at the electrode-electrolyte interface.
[0017] In any embodiment, the thickness of the polymer layer is 100 nm to 200 nm. Within the scope of the present application, the polymer layer can enhance the charge transfer process of Li+ / Na+ at the electrode-electrolyte interface without affecting the energy density of the battery.
[0018] A second aspect of the present application provides a method for manufacturing a negative electrode sheet as described above, the method comprising:
[0019] providing a negative electrode current collector;
[0020] Prepare a first slurry, and then apply it to the surface of the negative electrode current collector to form a conductive coating; and
[0021] A second slurry including porous particles is prepared and then made on the surface of the conductive coating to form the coating including porous particles. The manufacturing method of the present application is simple to operate, low in cost, highly practical, and suitable for large-scale production.
[0022] In any embodiment, the method includes forming a conductive coating having a thickness of 2 μm to 20 μm on at least one surface of the negative electrode current collector.
[0023] In any embodiment, the second slurry further includes a binder, and the second slurry includes 1 wt % to 10 wt % of the porous particles, based on the total weight of the porous particles and the binder.
[0024] In any embodiment, the method comprises forming a coating layer comprising porous particles having a thickness of 2 μm to 10 μm, or optionally 3 μm to 5 μm, on the conductive surface.
[0025] In any embodiment, the above method further includes: preparing a third slurry including a polymer, and then making the third slurry on the surface of the coating including porous particles to form a polymer layer, optionally the polymer includes a group that can form intermolecular forces with the molecules in the system in which it is located, and further optionally includes at least one of polyacrylic acid, polyacrylamide, polyacrylonitrile, and polyimide.
[0026] In any embodiment, the above method includes preparing the third slurry on the surface of the coating layer including porous particles to form a polymer layer having a thickness of 100 nm to 200 nm.
[0027] The third aspect of the present application provides a secondary battery, comprising a negative electrode sheet selected from the negative electrode sheet of the first aspect of the present application or a negative electrode sheet manufactured according to the method of the second aspect of the present application.
[0028] In any embodiment, the secondary battery is a negative electrode metal-free battery, optionally a negative electrode metal-free battery. Without being limited to any theory, in the secondary battery according to the present application, due to the longitudinally oriented growth of sodium dendrites, the provision of a coating including porous particles can particularly block their growth, thereby being able to more effectively inhibit sodium dendrites. Therefore, the negative electrode metal-free battery according to the present application has significant improvements in gas production and cycle life due to the inclusion of the negative electrode sheet of the present application.
[0029] A fourth aspect of the present application provides an electrical device, comprising the secondary battery of the third aspect of the present application.
[0030] The present application provides a negative electrode plate, which provides a larger expansion space by providing a coating including porous particles on the conductive coating, thereby alleviating the volume expansion caused by the metal deposition process, and can inhibit the generation of hydrogen and the occurrence of side reactions at the interface, effectively reducing the gas production of the battery; and provides more nucleation sites, the more sites there are, the more inclined to form a plane, thereby promoting the uniform deposition of lithium / sodium, and then inhibiting the generation of dendrites and dead lithium / sodium, which is beneficial to improving the cycle stability of the battery; and also accelerates the transmission of metal ions and improves the electrode reaction kinetic rate. Further, when using metal or metal oxide porous particles, it can also effectively reduce the nucleation overpotential of sodium and increase the hydrogen evolution overpotential, which is further beneficial to the uniform deposition of sodium metal and inhibits the generation and growth of sodium dendrites. Thus, the battery with the negative electrode plate described above is further improved in terms of gas production, cycle life, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is a scanning electron microscope image obtained by scanning the surface after step 1) in one embodiment of the present application.
[0032] Figure 2 This is a scanning electron microscope image obtained by scanning the surface after step 3) in one embodiment of the present application.
[0033] Figure 3 It is a schematic diagram of a battery cell according to an embodiment of the present application.
[0034] Figure 4 yes Figure 3 An exploded view of a battery cell according to an embodiment of the present application is shown.
[0035] Figure 5 is a schematic diagram of a battery module according to an embodiment of the present application.
[0036] Figure 6 It is a schematic diagram of a battery pack according to one embodiment of the present application.
[0037] Figure 7 yes Figure 6 An exploded view of a battery pack according to an embodiment of the present application is shown.
[0038] Figure 8 FIG. 1 is a schematic diagram of an electric device using a secondary battery according to an embodiment of the present application as a power source.
[0039] Description of reference numerals:
[0040] 1 battery pack; 2 upper box; 3 lower box; 4 battery module; 5 secondary battery; 51 shell; 52 electrode assembly; 53 top cover assembly DETAILED DESCRIPTION
[0041] Below, the negative electrode plate and its manufacturing method, secondary battery and electrical device of the present application are described in detail with appropriate reference to the drawings. However, there are cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0042] "Scope" disclosed in the present application is defined in the form of lower limit and upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a particular range. The scope defined in this way can be inclusive or exclusive of end values, and can be arbitrarily combined, i.e., any lower limit can be combined with any upper limit to form a range. For example, if a range of 60 to 120 and 80 to 110 is listed for a particular parameter, it is understood that a range of 60 to 110 and 80 to 120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following range can all be expected: 1 to 3, 1 to 4, 1 to 5, 2 to 3, 2 to 4 and 2 to 5. In the present application, unless otherwise specified, the numerical range "a to b" represents the abbreviation of any real number combination between a and b, wherein a and b are both real numbers. For example, the numerical range "0 to 5" means that all real numbers between "0 to 5" are listed in this document, and "0 to 5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0043] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0044] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0045] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0046] As mentioned above, negative electrode-free metal batteries have the advantages of cost advantage and commercialization and sustainable utilization in large-scale energy storage devices, but problems such as dendrite growth and uneven metal deposition still make the optimization of such metal batteries face many challenges. In order to solve the above defects in sodium metal batteries, some solutions have been proposed, such as improving the negative electrode structure, such as building a deposition framework on the current collector or depositing a coating to reduce the nucleation overpotential of sodium and avoid the formation of sodium dendrites. However, for the above improvements, either the process is complicated or strict control is required, making it difficult to implement industrially.
[0047] In view of this, the inventor proposes a negative electrode plate suitable for a negative electrode-free battery, which comprises a coating layer including porous particles disposed on a conductive coating layer. The present invention and preferred embodiments are described in more detail below.
[0048] Negative electrode
[0049] A first aspect of the embodiments of the present application provides a negative electrode plate.
[0050] The negative electrode sheet includes: a negative electrode current collector; a conductive coating disposed on at least one surface of the negative electrode current collector; and a coating including porous particles disposed on a surface of the conductive coating.
[0051] By setting a coating including porous particles, it provides a larger expansion space to alleviate the volume expansion caused by the metal deposition process, and at the same time provides more nucleation sites. The more sites there are, the more they tend to form planes, thereby promoting the uniform deposition of lithium / sodium, and then inhibiting the formation of dendrites and dead lithium / sodium, which is beneficial to improving the battery cycle stability.
[0052] Furthermore, after disassembling a battery including the coating of the porous particles of the present application, the presence of the porous particles can be observed by an inductively coupled device (CCD).
[0053] In some embodiments, the surface density of the coating is 0.002 g / 1540 m 2To 0.02g / 1540m 2 . In this application, the surface density of the coating has a meaning well known in the art and can be tested by methods known in the art. For example, a negative electrode sheet that has been coated on one side and dried by cold pressing can be punched into small discs with an area of S1, and its weight is weighed and recorded as M1. Then wipe off the porous coating of the negative electrode sheet after weighing, weigh the weight of the negative electrode current collector + conductive coating, and record it as M0. Surface density of coating = (M1-M0) / S1.
[0054] In some embodiments, the average particle size Dv50 of the porous particles is 0.2 μm to 10 μm, optionally 0.5 μm to 5 μm, such as 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, etc., for example, 0.5 μm to 2 μm. The volume average particle size Dv50 of the porous particles is a well-known meaning in the art, for example, it can be measured by particle size distribution-laser diffraction method and with reference to GB / T19077-2016 standard. For example, the particle sample is dispersed in a suitable liquid (for example, deionized water) or gas at a suitable concentration by ultrasound or other treatment, and is measured using a laser particle size analyzer (such as Malvern Master Size3000): the sample is passed through a monochromatic light beam (usually a laser), and when the light encounters the particles, it is scattered at different angles, and the scattered light is measured by a multi-element detector, and these values related to the scattering pattern are stored and used for subsequent analysis. Through appropriate optical models and mathematical processes, these quantitative scattering data are converted to obtain the percentage of particle volume on a series of discrete particle size segments relative to the total volume of the particles, thereby obtaining the particle size volume distribution. Among them, the Dv50 particle size represents the particle size corresponding to the cumulative volume distribution percentage of the particles reaching 50% from the small particle size side in the particle size distribution. The average particle size of the particles affects the thickness of the coating. In theory, the thickness of the coating should be as thin as possible to benefit the overall performance of the battery while achieving its above-mentioned functions, and can be optionally less than 10μm. The average particle size of the porous particles is within the above range, which is conducive to the formation of a coating with a thickness of less than 10μm.
[0055] In some embodiments, the porous particles have a porosity of 40% to 60%, and optionally have a porosity of 45% to 55%. The term "porosity (abbreviated as P)" has a well-known meaning in the art, and refers to the ratio of the pore volume in the material to the total volume, and the unit is %, and can be tested by instruments and methods well known in the art. For example, reference can be made to the GB / T 24586-2009 standard. For example, it can be determined as follows: using the inert gas (helium) replacement method of small molecular diameter, combined with Archimedes' principle and Bohr's law, the true volume of the material to be tested is accurately measured as the true volume of the sample, thereby obtaining the porosity of the sample to be tested;
[0056] Apparent volume V2 = S × H × A
[0057] Where:
[0058] S-area, cm 2 ;
[0059] H-thickness, cm;
[0060] A-sample number, EA;
[0061] V1 - true volume of sample, cm 3 , the test is obtained;
[0062] V2 - Sample apparent volume, cm 3 .
[0063] When the porosity of the porous particles of the present application is within this range, sufficient and stable expansion space is reserved for the volume change caused by metal deposition, which can effectively inhibit the generation of hydrogen at the interface and the occurrence of side reactions.
[0064] In some embodiments, the porous particles may be porous metals or porous metal oxides, inorganic porous materials and porous polymers. In some embodiments, the porous particles are porous metals or porous metal oxides. In some embodiments, the porous particles are inorganic porous materials. In some embodiments, the porous particles are porous polymers. In some embodiments, the porous metals or porous metal oxides include gold (Au), silver (Ag), platinum (Pt), zinc (Zn), zinc oxide (ZnO), copper (Cu), copper oxide (CuO), tin (Sn), tin oxide (SnO), antimony (Sb), antimony oxide (SbO), 2 O 3 , Sb 2 O 5 ), bismuth (Bi), bismuth oxide (Bi 2 O 3 ) and aluminum oxide (Al 2 O 3 ), these materials can be purchased from Global Jinxin (HQJX), for example. In some embodiments, the inorganic porous material includes at least one of porous carbon and porous ceramics, for example, these materials can be purchased from Zhongke Keyou. In some embodiments, the porous polymer includes at least one of porous polyacrylic acid, porous polyacrylamide, porous polyacrylonitrile, and porous polyimide, for example, these materials can be purchased from McLean. Optionally, in some specific embodiments, the porous particles include at least one of zinc (Zn), zinc oxide (ZnO), and copper (Cu). These materials are all commercially available, so the coating of the present application can be obtained at a lower cost.
[0065] In some embodiments, the thickness of the coating layer including porous particles is 2 μm to 10 μm, such as 3, 4, 5, 6, 7, 8, 9, 10 μm. In some embodiments, the thickness of the coating layer including porous particles may be 3 μm to 5 μm. Taking into account the effect of coating thickness on cost, gas production, and cycle life, while achieving the above functions, reducing the thickness of the coating layer as much as possible will be beneficial to the overall performance of the battery. When the coating thickness is within the above range, the coating is intact and not prone to cracks, which is Na + The deposition and its transport provide sufficient area and achieve a compromise between cost, gas production, cycle life, and keep the battery thickness within an appropriate range.
[0066] In some embodiments, the conductive coating includes a conductive agent. In the present application, the conductive agent used is not particularly limited. Optionally, the conductive agent includes at least one of carbon nanotubes, graphite, conductive carbon black, acetylene black, Ketjen black, carbon fiber or graphene. By providing a conductive coating on the current collector, the conductivity of the pole piece is improved, thereby reducing internal resistance, improving discharge efficiency and extending cycle life.
[0067] In addition, the conductive coating may also optionally include a binder. The binder is not particularly limited as long as it is suitable for the system environment of the present application. Specifically, the binder may be selected from at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), styrene-butadiene rubber (SBR), nitrile rubber (NBR), water-based acrylic resin, polyvinyl alcohol, polyvinyl butyral, polyurethane, fluorinated rubber, carboxymethyl cellulose (CMC), and polyacrylic acid (PAA). In addition, the conductive coating may also optionally include other additives, such as thickeners (such as sodium carboxymethyl cellulose (CMC-Na), but is not limited thereto.
[0068] In some embodiments, the thickness of the conductive coating is 2 μm to 20 μm, specifically, the thickness of the conductive coating can be 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 15 μm, 18 μm, etc. The thickness of the conductive coating is within this range, which will not cause excessive energy density loss, and can make the coating evenly distributed to play its corresponding role.
[0069] In some embodiments, the negative electrode plate further includes: a polymer layer disposed on the coating layer including porous particles. In some embodiments, the material of the polymer layer includes groups that can form intermolecular forces (such as hydrogen bonds, van der Waals forces, etc.) with molecules in the system in which it is located. In some specific embodiments, the material of the polymer layer may include at least one of polyacrylic acid, polyacrylamide, polyacrylonitrile and polyimide. For the polymer layer, due to the chain structure of the polymer used, it will not occupy the pores of the porous particles; and because it exists in the form of a polymer layer, it plays a role similar to a "filter membrane", selectively allowing particles of the size of Li+ / Na+ ions to pass through, thereby not affecting the porosity of the porous particles. In addition, since the polymer layer is uniformly coated on the electrode surface, the wettability of the electrolyte to the electrode is improved. Further, since the groups in the polymer (such as NH, C=O) can have strong intermolecular interactions with the electrolyte, such as hydrogen bonding, the charge transfer process of Li+ / Na+ at the electrode-electrolyte interface is accelerated. Through the combination of a coating including porous particles and a polymer layer, it is possible to synergistically enhance the deposition of metals at the electrode interface, the charge transfer kinetics during the dissolution process, and the reaction uniformity, while solving the problems of hydrogen evolution, dendrite growth, side reactions, and uneven deposition in the metal anode.
[0070] In some embodiments, the thickness of the polymer layer is 100 nm to 200 nm, such as 110, 115, 120, 125, 130, 135, 140, 145, 150, 155, 160, 165, 170, 175, 180, 185, 190 nm, etc. The electrode surface with a polymer coating thickness within this range still has a relatively dense internal structure in the later stage of the cycle, and the thickness hardly changes compared to the initial stage, thereby achieving a stable structure and excellent electrochemical performance.
[0071] Manufacturing method
[0072] A second aspect of the embodiments of the present application provides a method for manufacturing a negative electrode sheet as described above, which can manufacture the negative electrode sheet of the first aspect of the embodiments of the present application.
[0073] The method comprises the following steps:
[0074] 1) Providing a negative electrode current collector;
[0075] 2) preparing a first slurry, and then applying the slurry to the surface of the negative electrode current collector to form a conductive coating; and
[0076] 3) preparing a second slurry including porous particles, and then applying the second slurry to the surface of the conductive coating to form a coating including porous particles.
[0077] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0078] In some embodiments, the first slurry includes a conductive agent and a binder. In some embodiments, the first slurry may include, based on the total weight of the conductive agent and the binder, 1wt% to 40wt% of the conductive agent and 60wt% to 99wt% of the binder, and an appropriate amount of solvent. In some embodiments, the conductive agent may include at least one of carbon nanotubes, natural graphite, artificial graphite, conductive carbon black, acetylene black, Ketjen black, carbon fiber, and graphene.
[0079] In some embodiments, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), styrene-butadiene rubber (SBR), nitrile rubber (NBR), water-based acrylic resin, polyvinyl alcohol, polyvinyl butyral, polyurethane, fluorinated rubber, carboxymethyl cellulose (CMC), and polyacrylic acid (PAA).
[0080] In some embodiments, the solvent in the first slurry may be N-methylpyrrolidone (NMP).
[0081] In some embodiments, the manufacturing method used in step 2) may be coating, such as extrusion coating, gravure coating, etc.
[0082] In some embodiments, the thickness of the conductive coating formed in step 2) is 2 μm to 20 μm.
[0083] In some embodiments, the second slurry may include 1 wt% to 10 wt% of porous particles and 90 wt% to 99 wt% of binder, and an appropriate amount of solvent, based on the total weight of the porous particles and the binder. The content of the porous particles within the range of the present application can obtain a second slurry in which the porous particles are well dispersed, thereby facilitating obtaining a uniform coating.
[0084] In some embodiments, the porous particles have an average particle size Dv50 of 0.2 μm to 10 μm, optionally 0.5 μm to 5 μm, for example 0.5 μm to 2 μm; have a porosity of 40% to 60%, optionally 45% to 55%; can be selected from porous metals or porous metal oxides, inorganic porous materials and porous polymers; and can be optionally porous metals or porous metal oxides. The porous metals or porous metal oxides include gold (Au), silver (Ag), platinum (Pt), zinc (Zn), zinc oxide (ZnO), copper (Cu), copper oxide (CuO), tin (Sn), tin oxide (SnO), antimony (Sb), antimony oxide (SbO), 2 O 3 , Sb 2 O 5 ), bismuth (Bi), bismuth oxide (Bi 2 O 3 ) and aluminum oxide (Al 2 O 3 ), the inorganic porous material includes at least one of porous carbon and porous ceramics, and the porous polymer includes at least one of porous polyacrylic acid, porous polyacrylamide, porous polyacrylonitrile, and porous polyimide.
[0085] In some embodiments, the solvent in the second slurry may be NMP or the like.
[0086] In some embodiments, the manufacturing method used in step 3) may be coating, such as extrusion coating, transfer coating, etc.
[0087] In some embodiments, the porous particles may include at least one of zinc (Zn), zinc oxide (ZnO), and copper (Cu).
[0088] In some embodiments, the binder in step 3) may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), styrene-butadiene rubber (SBR), nitrile rubber (NBR), water-based acrylic resin, polyvinyl alcohol, polyvinyl butyral, polyurethane, fluorinated rubber, carboxymethyl cellulose (CMC), and polyacrylic acid (PAA).
[0089] In some embodiments, the method of the present invention further comprises: step 4), preparing a third slurry comprising a polymer, and then making the third slurry on the surface of the coating comprising porous particles to form a polymer layer. In some embodiments, the polymer may include at least one of polyacrylic acid, polyacrylamide, polyacrylonitrile, and polyimide.
[0090] In some embodiments, the solvent used in step 4) is NMP. Optionally, the third slurry comprises 10 wt% to 20 wt% of the polymer based on the total weight of the third slurry.
[0091] In some embodiments, the manufacturing method used in step 4) is coating, such as extrusion coating or transfer coating.
[0092] In some embodiments, through step 4), a polymer layer with a thickness of 100 nm to 200 nm is produced.
[0093] In addition, the secondary battery and the electric device of the present application will be described below with reference to the drawings.
[0094] Secondary battery
[0095] In one embodiment of the present application, a secondary battery is provided.
[0096] The term "secondary battery" mentioned herein refers to a battery cell, a battery module or a battery pack, which are described below.
[0097] Generally, a secondary battery cell includes a positive electrode sheet, a negative electrode sheet of the present invention, an electrolyte and a separator. During the battery charging and discharging process, active ions are embedded and removed back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is arranged between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.
[0098] [Positive electrode]
[0099] The positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer formed on at least a portion of the surface of the positive electrode current collector, wherein the positive electrode active material layer includes a positive electrode active material.
[0100] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.
[0101] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0102] In some embodiments, when the battery cell is a lithium-ion battery, the positive electrode active material may adopt a positive electrode active material for lithium-ion batteries known in the art. As an example, the positive electrode active material may include at least one of the following materials: a lithium-containing phosphate with an olivine structure, a lithium transition metal oxide, and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxides (such as LiCoO 2 ), lithium nickel oxide (such as LiNiO 2 ), lithium manganese oxide (such as LiMnO 2 、LiMn 2 O 4 ), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O 2 (Also referred to as NCM 333 )、LiNi 0.5 Co 0.2 Mn 0.3 O 2 (Also referred to as NCM 523 )、LiNi 0.5 Co 0.25 Mn 0.25 O 2 (Also referred to as NCM 211 )、LiNi 0.6 Co 0.2 Mn 0.2 O 2 (Also referred to as NCM 622 )、LiNi 0.8 Co 0.1 Mn 0.1 O 2 (Also referred to as NCM 811 ), lithium nickel cobalt aluminum oxide (such as LiNi 0.85 Co 0.15 Al 0.05 O 2 ) and its modified compounds, etc. Examples of lithium phosphates containing olivine structures may include, but are not limited to, lithium iron phosphate (such as LiFePO 4 (also referred to as LFP), composite materials of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO 4), at least one of a composite material of lithium manganese phosphate and carbon, a composite material of lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon.
[0103] The positive electrode active material may include at least one of a sodium transition metal oxide, a polyanionic compound and a Prussian blue compound. However, the present application is not limited to these materials, and other conventionally known materials that can be used as positive electrode active materials for sodium ion batteries may also be used.
[0104] As an optional technical solution of the present application, in the sodium transition metal oxide, the transition metal may be at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr and Ce. The sodium transition metal oxide is, for example, Na x MO 2 , wherein M is one or more of Ti, V, Mn, Co, Ni, Fe, Cr and Cu, 0 <x≤1。
[0105] As an optional technical solution of the present application, the polyanionic compound can be a compound having sodium ions, transition metal ions and tetrahedral (YO 4 ) n- A class of compounds with anionic units. The transition metal can be at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr and Ce; Y can be at least one of P, S and Si; n represents (YO 4 ) n- valence state.
[0106] The polyanionic compound can also be a compound having sodium ions, transition metal ions, tetrahedral (YO 4 ) n- The transition metal may be at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr and Ce; Y may be at least one of P, S and Si, and n represents (Y0 4 ) n- valence state; the halogen may be at least one of F, Cl and Br.
[0107] The polyanionic compound can also be a compound having sodium ions, tetrahedral (YO 4 ) n- Anion unit, polyhedral unit (ZO y ) m+ and an optional halogen anion. Y can be at least one of P, S and Si, and n represents (YO 4 ) n-Valence state: Z represents a transition metal, which can be at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr and Ce, and m represents (ZO y ) m+ valence state; the halogen may be at least one of F, Cl and Br.
[0108] Polyanionic compounds are, for example, NaFePO 4 、Na 3 V 2 (PO 4 ) 3 , NaM'PO4F (M' is one or more of V, Fe, Mn and Ni) and Na 3 (VO y ) 2 (PO 4 ) 2 F 3-2y At least one of (0≤y≤1).
[0109] The Prussian blue compound may be a compound having sodium ions, transition metal ions and cyanide ions (CN-). The transition metal may be at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr and Ce. The Prussian blue compound may be, for example, Na a Me b Me' c (CN) 6 , wherein Me and Me' are each independently at least one of Ni, Cu, Fe, Mn, Co and Zn, 0 <a≤2,0<b<1,0<c<1。
[0110] In some embodiments, the positive electrode active material layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.
[0111] In some embodiments, the positive electrode active material layer may further include a conductive agent, which may include, for example, at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0112] In some embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.
[0113] [Electrolytes]
[0114] The electrolyte plays the role of conducting ions between the positive electrode and the negative electrode. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or all-solid.
[0115] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.
[0116] In some embodiments, the electrolyte salt may be selected from at least one of sodium hexafluorophosphate, sodium bis(fluorosulfonyl)imide, sodium bis(trifluoromethanesulfonyl)imide, sodium trifluoromethanesulfonate, sodium tetrafluoroborate, sodium difluorophosphate, sodium perchlorate, and sodium chloride.
[0117] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.
[0118] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.
[0119] [Isolation film]
[0120] In some embodiments, the battery cell further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical stability and mechanical stability can be selected.
[0121] In some embodiments, the material of the isolation membrane can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.
[0122] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator may be formed into an electrode assembly by a winding process or a lamination process.
[0123] In some embodiments, the battery cell may include an outer packaging, which may be used to encapsulate the electrode assembly and the electrolyte.
[0124] In some embodiments, the outer packaging of the battery cell may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the battery cell may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0125] The present application has no particular limitation on the shape of the battery cell, which may be cylindrical, square or any other shape. Figure 3 The battery cell 5 is a square structure as an example.
[0126] In some embodiments, reference Figure 4 , the outer packaging may include a shell 51 and a cover plate 53. Among them, the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. The number of electrode assemblies 52 contained in the battery cell 5 can be one or more, and those skilled in the art can select according to specific actual needs.
[0127] In some embodiments, battery cells may be assembled into a battery module. The number of battery cells contained in the battery module may be one or more, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery module.
[0128] Figure 5 4 is an example of a battery module. Figure 5 In the battery module 4, the plurality of battery cells 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of battery cells 5 may be fixed by fasteners.
[0129] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of battery cells 5 are received in the receiving space.
[0130] In some embodiments, the battery modules described above may also be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery pack.
[0131] Figure 6 and Figure 7 1 is a battery pack 1 as an example. Figure 6 and Figure 7 The battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.
[0132] In addition, the present application also provides an electric device, which includes a secondary battery provided in the present application. The secondary battery can be used as a power source for the electric device, or as an energy storage unit for the electric device. The electric device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.
[0133] As the electrical device, a battery cell, a battery module or a battery pack can be selected according to its usage requirements.
[0134] Figure 8 The power consumption device is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the high power and high energy density requirements of the power consumption device for the secondary battery, a battery pack or a battery module can be used.
[0135] As another example, the device may be a mobile phone, a tablet computer, a notebook computer, etc. The device is usually required to be light and thin, and a battery cell may be used as a power source.
[0136] Example
[0137] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.
[0138] Example 1
[0139] Firstly, 20 wt% of carbon nanotubes, 80 wt% of polyvinylidene fluoride (PVDF) and a proper amount of NMP are mixed to form a slurry, and then a conductive coating with a thickness of 4 μm is formed on the surface of the copper foil by extrusion coating.
[0140] Then, 1wt% of porous copper particles (particle size of 0.2μm, porosity of 40%), 99wt% of polyvinylidene fluoride (PVDF) and an appropriate amount of NMP were evenly mixed to form a slurry, and then a porous copper coating with a thickness of 4μm was formed on the conductive coating obtained above by extrusion coating. After drying, the negative electrode sheet was obtained.
[0141] Example 2
[0142] The same method as in Example 1 was used except that porous copper particles having a particle size of 0.5 μm and a porosity of 40% were used.
[0143] Example 3
[0144] The same method as in Example 1 was used except that porous copper particles having a particle size of 1.0 μm and a porosity of 40% were used.
[0145] Example 4
[0146] The same method as in Example 1 was used except that porous copper particles having a particle size of 1.5 μm and a porosity of 40% were used.
[0147] Example 5
[0148] The same method as in Example 1 was used except that porous copper particles having a particle size of 2.0 μm and a porosity of 40% were used.
[0149] Example 6
[0150] The same method as in Example 1 was used except that porous copper particles having a particle size of 5.0 μm and a porosity of 40% were used, and a porous copper coating having a thickness of 5 μm was formed on the conductive coating.
[0151] Example 7
[0152] The same method as in Example 1 was used, except that porous copper particles having a particle size of 10 μm and a porosity of 40% were used, and a porous copper coating having a thickness of 10 μm was formed on the conductive coating.
[0153] Example 8
[0154] The same method as in Example 1 was used except that porous copper particles having a particle size of 1.0 μm and a porosity of 45% were used.
[0155] Example 9
[0156] The same method as in Example 1 was used except that porous copper particles having a particle size of 1.0 μm and a porosity of 50% were used.
[0157] Example 10
[0158] The same method as in Example 1 was used except that porous copper particles having a particle size of 1.0 μm and a porosity of 55% were used.
[0159] Embodiment 11
[0160] The same method as in Example 1 was used except that 2 wt % of porous copper particles having a particle size of 1.0 μm and a porosity of 60% and 98 wt % of polyvinylidene fluoride (PVDF) were used.
[0161] Example 12
[0162] The same method as in Example 1 was used except that 5 wt % of porous copper particles having a particle size of 2.0 μm and a porosity of 40% and 95 wt % of polyvinylidene fluoride (PVDF) were used.
[0163] Example 13
[0164] The same method as in Example 1 was used except that 10 wt % of porous copper particles having a particle size of 1.0 μm and a porosity of 50% and 90 wt % of polyvinylidene fluoride (PVDF) were used.
[0165] Embodiment 14
[0166] The same method as in Example 1 was used except that 6 wt % of porous copper oxide particles having a particle size of 1.0 μm and a porosity of 50% and 94 wt % of polyvinylidene fluoride (PVDF) were used.
[0167] Embodiment 15
[0168] The same method as in Example 1 was used except that 5 wt % of porous zinc particles having a particle size of 1.0 μm and a porosity of 50% and 95 wt % of polyvinylidene fluoride (PVDF) were used.
[0169] Example 16
[0170] The same method as in Example 1 was used except that 6 wt % of porous tin particles having a particle size of 1.0 μm and a porosity of 50% and 94 wt % of polyvinylidene fluoride (PVDF) were used.
[0171] Embodiment 17
[0172] The same method as in Example 1 was used except that 6 wt % of porous polyacrylic acid particles having a particle size of 1.0 μm and a porosity of 50% and 94 wt % of polyvinylidene fluoride (PVDF) were used.
[0173] Embodiment 18
[0174] The same method as in Example 1 was used except that 6 wt % of porous ceramic particles having a particle size of 1.0 μm and a porosity of 50% and 94 wt % of polyvinylidene fluoride (PVDF) were used.
[0175] Embodiment 19
[0176] Step 1): 20 wt% of carbon nanotubes, 80 wt% of polyvinylidene fluoride (PVDF) and an appropriate amount of NMP are mixed to form a slurry, and then a conductive coating with a thickness of 4 μm is formed on the surface of the copper foil by extrusion coating.
[0177] Step 2): 1 wt% of porous copper particles (particle size of 0.2 μm, porosity of 40%), 99 wt% of polyvinylidene fluoride (PVDF) and an appropriate amount of NMP are mixed evenly to form a slurry, and then a porous copper coating with a thickness of 4 μm is formed on the conductive coating obtained above by extrusion coating, and then dried.
[0178] Step 3): Prepare a slurry of 10 wt% polyacrylic acid in NMP, and apply it by extrusion coating to form a polyacrylic acid coating with a thickness of 150 nm on the porous copper coating, and then dry to obtain a negative electrode sheet.
[0179] Embodiment 20
[0180] The process is carried out in the same manner as in Example 19, except that 1 wt % of porous copper particles (particle size 10 μm, porosity 60%) are used in step 2) to obtain a coating including porous copper with a thickness of 10 μm, and 10 wt % of a slurry of polyacrylamide in NMP is used in step 3).
[0181] Embodiment 21
[0182] The process was carried out in the same manner as in Example 19, except that 1 wt % of porous copper particles (particle size 2.0 μm, porosity 55%) were used in step 2) and 15 wt % of a slurry of polyacrylonitrile in NMP was used in step 3).
[0183] Embodiment 22
[0184] The process was carried out in the same manner as in Example 19, except that 1 wt % of porous copper particles (particle size 0.5 μm, porosity 45%) were used in step 2) and 20 wt % of a slurry of polyimide in NMP was used in step 3).
[0185] Comparative Example 1
[0186] 20wt% carbon nanotubes, 80wt% polyvinylidene fluoride (PVDF) and an appropriate amount of NMP were mixed to form a slurry, and then a conductive coating with a thickness of 4 μm was formed on the surface of the copper foil by extrusion coating, and the negative electrode was obtained after drying.
[0187] Comparative Example 2
[0188] 20wt% carbon nanotubes, 80wt% polyvinylidene fluoride (PVDF) and an appropriate amount of NMP were mixed to form a slurry, and then a conductive coating with a thickness of 4μm was formed on the surface of the porous copper foil by extrusion coating, and the negative electrode was obtained after drying.
[0189] Comparative Example 3
[0190] Step 1): 20 wt% of carbon nanotubes, 80 wt% of polyvinylidene fluoride (PVDF) and an appropriate amount of NMP are mixed to form a slurry, and then a conductive coating with a thickness of 4 μm is formed on the surface of the copper foil by extrusion coating;
[0191] Step 2): 1wt% copper particles (non-porous) are mixed with 99wt% polyvinylidene fluoride (PVDF) and an appropriate amount of deionized water to form a slurry, and then a copper coating with a thickness of 4μm is formed on the conductive coating obtained above by extrusion coating. After drying, the negative electrode sheet is obtained.
[0192] Table 1 below shows a summary of the conditions of Examples 1 to 22 and Comparative Examples 1 to 3 described above.
[0193] Table 1
[0194]
[0195]
[0196] Note: “ / ” means does not exist.
[0197] Characterization of coatings
[0198] Morphological characterization
[0199] The surfaces obtained in each step of Examples 1 to 22 were scanned using a scanning electron microscope (SEM). Figure 1 The scanning electron microscope image obtained by scanning the surface after step 1) of Example 19 is shown, Figure 2 The SEM image obtained by scanning the surface after step 3) of Example 19 is shown. Figure 1 and Figure 2It can be seen that after coating the conductive coating, the surface is relatively flat, while after coating the coating including porous particles and the polymer layer, the surface becomes uneven, which greatly increases the nucleation sites.
[0200] Furthermore, after disassembling the battery prepared in Example 19, the presence of porous Cu particles was observed by CCD.
[0201] Area Density
[0202] The obtained negative electrode sheet is punched into small discs with an area of S1, and its weight is recorded as M1. Then the porous coating of the weighed negative electrode sheet is wiped off, and the weight of the negative electrode current collector + conductive coating is weighed and recorded as M0. The surface density of the coating = (M1-M0) / S1.
[0203] Each sample was tested 3 times and the average value was taken. The results are shown in Table 2.
[0204] Preparation of anode-free sodium metal batteries
[0205] Preparation of positive electrode sheets: The positive electrode active material sodium ferric pyrophosphate, the conductive agent carbon nanotubes, and the binder polyvinylidene fluoride (PVDF) are fully stirred and mixed in a proper amount of N-methylpyrrolidone (NMP) at a mass ratio of 95:2:3 to form a uniform positive electrode slurry; the positive electrode slurry is coated on the surface of the positive electrode current collector aluminum foil, and after drying, cold pressing, and die-cutting, a positive electrode sheet with a thickness of 200 μm is obtained.
[0206] Preparation of electrolyte: In an argon-filled glove box with a water content of <1 ppm, diethylene glycol dimethyl ether and tetrahydrofuran were mixed in a mass ratio of 1:3, and sodium hexafluorophosphate (NaPF 6 ), and after stirring evenly, an electrolyte is obtained.
[0207] Preparation of a negative electrode-free sodium metal battery: stack the positive electrode sheet, the isolation membrane, and the negative electrode sheets obtained in Examples 1 to 22 and Comparative Examples 1 to 3 prepared in the above steps in order, so that the isolation membrane is located between the positive electrode sheet and the negative electrode sheet and can isolate the positive electrode sheet from the negative electrode sheet; then wind the stacked components to obtain an electrode assembly; place the electrode assembly in a shell, and inject an electrolyte after drying; and obtain a negative electrode-free sodium metal battery after processes such as formation and standing.
[0208] Performance Testing
[0209] Storage gas production: The secondary battery prepared above is arranged along the sealing nail welding hole with a pipeline, the diameter of the pipeline is the same as the sealing nail hole, and the oil gauge is connected along the end of the pipeline. The battery is clamped with 2 aluminum plates, and the initial clamp force is set to 3000N. Calibration is performed three times, each with an interval of 15 minutes; then the battery is fully charged to 100% SOC, and the temperature of all cells is monitored, and the oil gauge pressure is recorded every day. The results are shown in Table 2 below. The storage gas production results are expressed as the number of days it takes for the oil gauge pressure to reach 0.35Mpa.
[0210] Cyclic gas production: Arrange a pipeline along the sealing nail welding hole of the secondary battery prepared above, the diameter of the pipeline is the same as the sealing nail hole, connect the oil gauge along the end of the pipeline, clamp the battery with 2 aluminum plates, set the initial clamp force to 3000N, and calibrate three times, each time with an interval of 15 minutes; then charge and discharge the battery at 1C / 1C, monitor the temperature of all cells, and record the oil gauge pressure every day. The results are shown in Table 2 below. Among them, the results of cyclic gas production are expressed by the number of cycles used for the oil gauge pressure to reach 0.65Mpa.
[0211] Cycle life: Take five battery cells in each of the above embodiments and comparative examples for parallel testing. Each battery cell is charged at a rate of 0.33C at room temperature until the voltage is equal to 3.65V, and then discharged at a rate of 0.33C until the voltage is equal to 1.5V. The reversible capacity is measured as C0. Repeat the charging and discharging until the discharge capacity Cn / C0 of a certain cycle is 80%. The total number of cycles is recorded as X-Cycle. Among them, Cn is the reversible capacity at the nth cycle. The results are shown in Table 2 below.
[0212] Table 2: Summary and comparison of test results
[0213]
[0214]
[0215] Based on Examples 1 to 7, it can be seen that by setting a coating of porous particles with a particle size within the scope of this application, the storage gas production at 25°C is not less than 950D / 0.35Mpa, the cycle gas production at 25°C is not less than 800cls / 0.65Mpa, and the cycle life at 25°C is not less than 1530cls. Compared with Comparative Example 1, the embodiments of the present application increase the number of days required to reach 0.35Mpa by at least 27.6%, and the number of cycles required to reach 0.65Mpa by at least 15.9%, significantly reducing the storage gas production and cycle gas production of the battery.
[0216] Based on Examples 3, 8 to 10, it can be seen that by providing a coating of porous particles with a porosity within the range of the present application, the cycle gas production, storage gas production and cycle life of the battery are significantly improved. Even when the particle size of the porous particles is 1.0 μm and the porosity is 50%, compared with Comparative Example 1, the number of days required to reach 0.35 MPa is increased by at least 200%, and the number of cycles required to reach 0.65 MPa is increased by at least 160%.
[0217] Based on the comparison between Example 9, Example 13 and Example 14 and Example 3 and Example 12, it can be seen that the cycle gas generation, storage gas generation and cycle life of the battery are significantly improved by setting the coating with the content of porous particles within the scope of the present application.
[0218] Examples 13 to 18 show that coatings of different porous materials improve the cycle gas generation, storage gas generation and cycle life of the battery.
[0219] Examples 19 to 22 show that, in the case of adding a polymer layer, the cycle gas generation, storage gas generation and cycle life of the battery can also be significantly improved. From the values in Table 2 above, it can be seen that the provision of the polymer layer further improves the performance of the battery, which indicates that the combination of the coating of the porous particles and the polymer layer can synergistically enhance the deposition of the metal at the electrode interface, the charge transfer kinetics and the reaction uniformity during the dissolution process.
[0220] For Comparative Example 2, it also improves the storage and circulation gas production performance and cycle life to a certain extent. However, in practice, the porous copper substrate will significantly reduce the strength of the copper material, making it very easy to have the risk of substrate cracking during the cycle after being assembled into a full battery, thereby bringing greater safety hazards in application. In contrast, there is no such hazard in Examples 1 to 22. Moreover, compared with Comparative Example 2, although the storage gas production and circulation gas production of Examples 1 and 7 are equivalent to or slightly different from Comparative Example 2, their cycle life is better than Comparative Example 2, while Examples 2-6 and 8-22 of the present application have comparable effects or obvious improvements in storage gas production, circulation gas production and cycle life.
[0221] A metal layer is provided on the conductive coating, such as a coating including non-porous copper particles, as in Comparative Example 3, which can also improve the storage gas production and cycle gas production performance to a certain extent, but it deteriorates the cycle life to a certain extent. Without wishing to be limited by any theory, when the dynamic evolution process of conventional corrosion-resistant metal coatings (such as Comparative Example 3) and electrode coatings including porous particles (Examples 1 to 22) at different sodium metal deposition-dissolution stages is analyzed using SEM and EDS, both electrode surfaces show a uniformly distributed interface layer, but after 10cls of cycles, the metal surface of the negative electrode of Comparative Example 3 becomes uneven and obvious cracks appear, while the negative electrode plate of the present application still maintains a relatively complete interface layer after continuous cycles, and the coating of porous particles is similar to a stable "sieve", which plays a role in regulating the uniform deposition and dissolution of sodium on the surface of the composite electrode, thereby extending the cycle life of the battery. And the pole piece of the present application has obvious advantages in terms of cycle performance.
[0222] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A negative electrode plate, characterized in that: The negative electrode plate comprises: Anode current collector; a conductive coating disposed on at least one surface of the negative electrode current collector; and A coating including porous particles is disposed on a surface of the conductive coating.
2. The negative electrode sheet according to claim 1, wherein: The surface density of the coating layer including the porous particles is 0.002 g / 1540 m 2 To 0.02g / 1540m 2 .
3. The negative electrode sheet according to claim 1 or 2, wherein: The average particle size Dv50 of the porous particles is 0.2 μm to 10 μm, and optionally 0.5 μm to 5 μm.
4. The negative electrode sheet according to any one of claims 1 to 3, wherein: The porous particles have a porosity of 40% to 60%, optionally 45% to 55%.
5. The negative electrode sheet according to any one of claims 1 to 4, wherein: The porous particles include at least one of porous metals or porous metal oxides, inorganic porous materials, and porous polymers; and optionally include at least one of porous metals or porous metal oxides.
6. The negative electrode sheet according to claim 5, wherein: The porous metal or porous metal oxide includes at least one of gold, silver, platinum, zinc, zinc oxide, copper, copper oxide, tin, tin oxide, antimony, antimony oxide, bismuth, bismuth oxide and aluminum oxide; the porous inorganic material includes at least one of porous carbon and porous ceramics; and the porous polymer includes at least one of porous polyacrylic acid, porous polyacrylamide, porous polyacrylonitrile and porous polyimide.
7. The negative electrode sheet according to any one of claims 1 to 6, wherein: The coating layer comprising porous particles has a thickness of 2 μm to 10 μm, optionally 3 μm to 5 μm.
8. The negative electrode sheet according to any one of claims 1 to 7, wherein: The coating layer including porous particles includes 1 wt % to 10 wt % of the porous particles.
9. The negative electrode sheet according to any one of claims 1 to 8, wherein: The conductive coating includes a conductive agent. Optionally, the conductive agent includes at least one of carbon nanotubes, graphite, conductive carbon black, acetylene black, Ketjen black, carbon fiber, and graphene.
10. The negative electrode sheet according to any one of claims 1 to 9, wherein: The conductive coating has a thickness of 2 μm to 20 μm.
11. The negative electrode sheet according to any one of claims 1 to 10, wherein: The negative electrode plate further includes: a polymer layer disposed on the coating layer including porous particles, optionally, the material of the polymer layer includes groups that can form intermolecular forces with molecules in the system in which it is located, and further optionally, the material of the polymer layer includes at least one of polyacrylic acid, polyacrylamide, polyacrylonitrile and polyimide.
12. The negative electrode sheet according to claim 11, wherein: The polymer layer has a thickness of 100 nm to 200 nm.
13. A method for manufacturing a negative electrode sheet, comprising the following steps: providing a negative electrode current collector; Prepare a first slurry, and then apply it to at least one surface of the negative electrode current collector to form a conductive coating; and A second slurry including porous particles is prepared and then applied to the surface of the conductive coating to form a coating including porous particles.
14. The method according to claim 13, wherein: The method includes forming a conductive coating having a thickness of 2 μm to 20 μm on at least one surface of the negative electrode current collector.
15. The method according to claim 13 or 14, wherein: The second slurry further includes a binder, and the second slurry includes 1 wt % to 10 wt % of the porous particles based on the total weight of the porous particles and the binder.
16. The method according to any one of claims 13 to 15, wherein: The method comprises forming a coating layer including porous particles having a thickness of 2 μm to 10 μm, optionally 3 μm to 5 μm, on the conductive surface.
17. The method according to any one of claims 13 to 16, further comprising: A third slurry including a polymer is prepared, and then the third slurry is made on the surface of the coating including porous particles to form a polymer layer. Optionally, the polymer includes a group that can form intermolecular forces with molecules in the system in which it is located, and further optionally includes at least one of polyacrylic acid, polyacrylamide, polyacrylonitrile, and polyimide.
18. The method according to claim 17, wherein: The method includes preparing the third slurry on the surface of the coating layer including the porous particles to form a polymer layer having a thickness of 100 nm to 200 nm.
19. A secondary battery, characterized in that: The invention comprises the negative electrode sheet according to any one of claims 1 to 12 and the negative electrode sheet obtained by the method according to any one of claims 13 to 18.
20. The secondary battery according to claim 19, wherein The secondary battery is a negative electrode-free metal battery, optionally a negative electrode-free sodium metal battery.
21. An electrical device, characterized in that: Includes the secondary battery according to claim 19 or 20.